The sources and Sitz im Leben of Matthew 23 - Newport, Kenneth G. C. (Journal for the study of the New Testament. Supplement series ;, 1995)
Matthew 23 presents the New Testament scholar with many problems. Not the least of these is the unequivocal acceptance of Pharisaic authority in vv. 2-3. In the same chapter the tithing of mint, dill and cummin is affirmed (v. 23) and the altar is said still to sanctify the gift (v. 19). This material seems out of place within the broader context of Matthew's Gospel. This study examines the origin and function of such material and argues that the bulk of the chapter (vv. 2-31) is formed from a single unified source and cannot be explained in terms of Matthew's editing of Q, M and Markan materi.